HEIDEGGER: UNDERSTANDING AND INTERPRETATION AS DAS SEIN EXISTENTIAL (Analysis of Verses of God's Appreciation on Humans in Tafsir Ibn Katsīr) - A.F. Udin; S. Bahri (PT. Hafasy Dwi Nawasena, 2024)
Recently, hermeneutics has become a study that has attracted the attention of observers of al-Qur’an and Tafsir. One of its studies is Heidegger's hermeneutics. In brief, there are four main things in Gadamer's hermeneutics, namely facticity, understanding, ontological-existential relations, and time. This literature research aims to discuss Ibn Katsīr's interpretation which is analyzed from Heidegger's hermeneutics. The results of the research show that Ibnu Katsīr has been influenced by socio-cultural conditions or what is called facticity. Second, there is pre-understanding, and third, the openness of the interpreter in the context of further interpretation. Implicitly, Ibn Katsīr was becoming das sein existing in the understanding itself.